PENDAMPINGAN PENCATATAN DAN PEMBUKUAN SEDERHANA BAGI KELOMPOK UMKM DI KELURAHAN MELAYU KOTA PIRING - Ranti Utami; Muhammad Isa Alamsyahbana; Afriyadi Afriyadi; Henisha Auliananda; Kinanti Rahmadhani; Lina Oktafiani; Mohamad Hammam Pardiansyah; Novita Kristiani Waruwu; Nurul Despurnama Sary; Salsabil Nabila Arifin; Sasrya Elsana; Dian Ocviasari; Dandy Lucky Pratama (Bajang Institute, 2023)
One of the most important business sectors for economic development is Micro, Small and Medium Enterprises (MSMEs). However, MSME actors are still not aware of the development of the financial aspect. This is due to the lack of motivation and ability of MSME actors in managing their business finances. The purpose of this community service activity is to provide assistance to MSME actors regarding simple recording and bookkeeping so that in the future MSME actors master the basics and procedures for recording and simple bookkeeping so that they can make good financial reports. The method used is by way of mentoring. The results obtained from this activity are that MSME actors have new insights and abilities in carrying out this simple recording and bookkeeping